2009
DOI: 10.1002/cne.22061
|View full text |Cite
|
Sign up to set email alerts
|

Neural reconnection in the transected spinal cord of the freshwater turtle Trachemys dorbignyi

Abstract: This paper provides the first evidence that fresh water turtles are able to reconnect their completely transected spinal cord leading to some degree of recovery of the motor functions lost after injury. Videographic analysis showed that some turtles (5 out of 11) surviving more than 20 days after injury were able to initiate stepping locomotion. However the stepping movements were slower than those of normal animals and swimming patterns were not restored. Even though just 45% of the injured turtles recovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 55 publications
8
75
0
Order By: Relevance
“…Profuse sprouting and branching of numerous serotonergic axons has been also observed at the site of spinal cord injury in the freshwater turtle Trachemys dorbignyi [Rehermann et al, 2009]. Interestingly, the recent study from Silver's group has shown that aft er a thermocoagulatory lesion in the rat frontoparietal cortex, serotonergic axons persist within the lesion edge and, by the third week post-injury, sprout robustly into the lesion cavity, whereas callosal axons become dystrophic and die back [Hawthorne et al, 2011].…”
Section: Brain Behavior and Evolution )mentioning
confidence: 97%
“…Profuse sprouting and branching of numerous serotonergic axons has been also observed at the site of spinal cord injury in the freshwater turtle Trachemys dorbignyi [Rehermann et al, 2009]. Interestingly, the recent study from Silver's group has shown that aft er a thermocoagulatory lesion in the rat frontoparietal cortex, serotonergic axons persist within the lesion edge and, by the third week post-injury, sprout robustly into the lesion cavity, whereas callosal axons become dystrophic and die back [Hawthorne et al, 2011].…”
Section: Brain Behavior and Evolution )mentioning
confidence: 97%
“…During development, astrocyte precursors support growing axons (Rakic, 1971; McDermott et al, 2005) and after SCI in lower vertebrates and very young mammals, astrocyte progenitors migrate from the ependymal zone to form a scaffold for regeneration (Chernoff et al, 2003; Fry et al, 2003; Rehermann et al, 2009). However, after SCI in adult mammals, astrocytes vacate the lesion core (Fitch et al, 1999) and form a cellular and molecular border at the lesion edge that is inhibitory to axon growth (Reier et al, 1983; Liuzzi and Lasek, 1987; Rudge and Silver, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…As in the other regenerative non-mammalian species discussed above, after SCI, glial cell processes grew parallel to the long axis of the spinal cord. At the same time, phagocytic macrophages were observed at the lesion (Rehermann et al, 2009). Studies are just beginning to explore cellular aspects of neurogenesis and molecular programs influencing regeneration in this organism (Garcia et al, 2012; Rehermann et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…A few recent studies have also demonstrated axon regeneration after complete spinal cord transection in the turtle (Garcia et al, 2012; Rehermann et al, 2009; Rehermann et al, 2011). After injury, axon regeneration, primarily of propriospinal and sensory neurons, is followed by partial restoration of locomotion in ~50% of spinalized turtles (Rehermann et al, 2009; Rehermann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation